Penerapan Insolvency Test dengan Metode Cash Flow Test dan The Balance Sheet Test dalam Memutus Kepailitan di Indonesia - Reiner Multiwijaya (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study explores the application of the insolvency test—specifically the cash flow test and balance sheet test—in bankruptcy proceedings in Indonesia. Although Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU) outlines the basic framework for bankruptcy, it lacks explicit provisions regarding the insolvency test mechanism. Using a normative juridical method and a conceptual approach, supported by statutory analysis, this research evaluates the effectiveness of these tests in determining a debtor’s insolvency status. The findings indicate that the cash flow test is better suited for assessing short-term liquidity, while the balance sheet test offers insight into long-term so lvency. However, practical implementation faces challenges such as inconsistent legal interpretation and the absence of standardized guidelines. Despite not being formally integrated into the Indonesian legal system, the insolvency test holds significant potential to improve the objectivity and fairness of court rulings. A clearer and more consistent application of these methods could enhance legal protection for debtors and promote a more balanced bankruptcy system.